Abnormal functional connectivity of the striatum in first‐episode drug‐naive early‐onset Schizophrenia. Issue 5 (5th April 2022) - Zhang, Yan; Peng, Yue; Song, Yichen; Zhou, Youqi; Zhang, Sen; Yang, Ge; Yang, Yongfeng; Li, Wenqiang; Yue, Weihua; Lv, Luxian; Zhang, Dai
Abstract: Abnormal brain network connectivity is strongly implicated in the pathogenesis of schizophrenia. The striatum, consisting of the caudate and putamen, is the major treatment target for antipsychotics, the primary treatments for schizophrenia; however, there are few studies on the functional connectivity (FC) of striatum in drug‐naive early‐onset schizophrenia (EOS) patients. We examined the FC values of the caudate nucleus and putamen with whole brain by resting‐state functional magnetic resonance imaging (RS‐fMRI) and the associations with indices of clinical severity. Patients demonstrated abnormal FC between subregions of the putamen and both the visual network (left middle occipital gyrus) and default mode network (bilateral anterior cingulate, left superior frontal, and right middle frontal gyri). Furthermore, FC between dorsorostral putamen and left superior frontal gyrus correlated with both positive symptom subscore and total score on the Positive and Negative Syndrome Scale (PANSS). These findings demonstrate abnormal FC between the striatum and other brain areas even in the early stages of schizophrenia, supporting neurodevelopmental disruption in disease etiology and expression. Abstract : We examined the functional connectivity of the caudate nucleus and putamen with whole brain in early‐onset schizophrenia by resting‐state functional magnetic resonance imaging and the associations with indices of clinical severity.